AAV9-Mediated Overexpression of TRPM4 Increases the Incidence of Stress-Induced Ventricular Arrhythmias in Mice - Pironet, Andy; Syam, Ninda; Vandewiele, Frone; Van den Haute, Chris; Kerselaers, Sara; Pinto, Silvia; Vande Velde, Greetje; Gijsbers, Rik; Vennekens, Rudi (Frontiers in Physiology, 2019)
Ca2+ activated non-selective cation channels have been described in cardiomyocytes since the advent of the patch clamp technique. It has been hypothesized that this type of ion channel contributes to the triggering of cardiac arrhythmias. TRPM4 is to date the only molecular candidate for a Ca2+ activated non-selective cation channel in cardiomyocytes. Its significance for arrhythmogenesis in living animals remains however unclear. In this study, we have tested whether increased expression of wild-type (WT) TRPM4 augments the risk of arrhythmias in living mice. Overexpression of WT TRPM4 was achieved via tail vein injection of adeno-associated viral vector serotype 9 (AAV9) particles, which have been described to be relatively cardiac specific in mice. Subsequently, we performed ECG-measurements in freely-moving mice to determine their in vivo cardiac phenotype. Though cardiac muscle was transduced with TRPM4 viral particles, the majority of viral particles accumulated in the liver. We did not observe any difference in arrhythmic incidents during baseline conditions. Instead, WT mice that overexpress TRPM4 were more vulnerable to develop premature ventricular ectopic beats during exercise-induced -adrenergic stress. Conduction abnormalities were rare and not more frequent in transduced mice compare to WT mice. Taken together, we provide evidence that overexpression of TRPM4 increases the susceptibility of living mice to stress-induced arrhythmias.